Structural Color Controllable Humidity Response Chiral Nematic Cellulose Nanocrystalline Film - Ran Duan; Mengli Lu; Ruiqi Tang; Yuanyuan Guo; Dongyu Zhao (Biosensors, 2022)
Through self-assembly, environmentally friendly cellulose nanocrystals (CNCs) can form films with a photonic crystal structure whose pitch size can be adjusted in a variety of ways at the fabrication stage. Moreover, the films exhibit response performance to multiple stimuli, which offers extensive applications. Poly(ethylene glycol) (PEG) and CNCs combine to form a smaller chiral nematic domain that develops a solid film with a uniform spiral structure when slowly dried. By changing the composition of CNCs and PEG, flexible and flat photonic composite films with uniform structural colors from blue to red are prepared. Benefiting from the change in pitch size by insertion and detachment of water molecules into the chiral nematic structure, CNCs films and CNC-PEG composite films exhibit a reversible structural color change in response to different humidity. In addition, the chiral nematic films formed by the combination of glycerol and CNCs have a reversible stimulation response to hydrochloric acid gas. Similarly, adjusting the ratio of glycerol can control the pitch size of the films and, thus, the reflective color. In summary, the pitch size of the photonic crystal structure of the films can be precisely tuned by regulating the additive ratio, and the two prepared films have reversible responses to humidity and hydrochloric acid gas, respectively. The CNC-based films show promise in the application of colorimetric biosensors.